PENGARUH PENGGUNAAN GAMBAR DALAM MENGAJAR MENULIS DESKRIPTIF TEKS SISWA TAHUN KEDUA SMPN 1 SIAK HULU - Melia Sesrica; Jismulatif '; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out whether there is a significant effect of using pictures in teaching writing descriptive text of the second year students of SMPN 1 Siak Hulu in the Academic Year 2016/2017 in writing descriptive text. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design. This research used one group pretest-posttest design. The instrument used in this research was tests (pretest and posttest). The population of this research was 296 of the Second Year Students of SMPN 1 Siak Hulu and the sample of this research is the VIII E of SMPN 1 Siak Hulu which is total number of students of class is 35 students. The data of this research were collected by giving the writing test about descriptive text (pretest-posttest) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed the mean score of pretest was 48.57 and the mean score of posttest was 58.95. Based on the data analysis, It can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It also meant that teaching writing by using pictures technique was effective to improve students’ writing ability especially in descriptive text.Keywords: Pictures, Writing, Descriptive Text